A Comprehensive Review of the Pharmacological Potential of Green Synthesized Nanoparticles from Calotropis procera - Bhardwaj, Gauri Shankar; Jain, Aditya; Jangid, Tanvi; Jangir, Ram Niwas (Pharmacognosy Reviews)
Calotropis procera is a versatile plant widely recognized for its applications in traditional medicine, fodder, fuel, timber, fibre production, and phytoremediation. In recent years, it has also gained attention in nanotechnology research as a green source for nanoparticle synthesis. Green-synthesized nanoparticles have emerged as a major focus due to their environmentally friendly, sustainable, and biocompatible nature. Among various biological sources, plants like C. procera are commonly employed for nanoparticle synthesis owing to their inherent safety, rich phytochemical profile, and ecological benefits. This review summarizes in-depth analysis of global research on Calotropis procera-based nanoparticles by examining literature from major scientific databases, including PubMed, Scopus, Web of Science, and Google Scholar, covering studies published up to 2025. This review provides a comprehensive overview of the botanical characteristics, key phytochemical constituents, and traditional uses of Calotropis procera. It also explores the different types of nanoparticles synthesized from C. procera and their major pharmacological activities, including antimicrobial, antidiabetic, anti-inflammatory, anti-cancerous, larvicidal, immunomodulatory, anti-hypertensive, anti-oxidant and hepatoprotective activity, as well as the toxicity profile of C. procera-derived green nanoparticles. In conclusion, nanoparticles synthesized from Calotropis procera hold significant promise as therapeutic agents due to their diverse pharmacological properties. Through this review, a strong platform is established for future research on C. procera-based nanoparticles for clinical and other applications.
Keywords: Calotropis procera; Green synthesized Nanoparticles; Pharmacological Properties; Phytochemical Composition; Toxicity